Dr. Brad Has Gone Mad! - Gutman, Dan; Paillot, Jim (New York, NY Scholastic Inc., 2016)
Ella Mentry School counselor Dr. Brad believes wisecracking A.J. may be a genius and subjects him to some very weird tests to find out for sure.
110804
Keywords: Schools -- Juvenile fiction; Counselors -- Juvenile fiction; Psychological tests; Juvenile fiction; Humorous fiction